2016
DOI: 10.1002/admi.201600441
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Force Sensors: From Fundamental Concepts toward Applications in Cell Biology

Abstract: Mechanical signals are central for the regulation of developmental, physiological, and pathological processes within biological systems. Force transduction across the cell–extracellular matrix (ECM) interface is highly crucial for regulating cell fate via mechanosensing and mechanotransduction cascades. The key molecules involved in these highly sophisticated processes have been identified in recent years. But little is still known about their interactions and in particular the molecular forces that determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 165 publications
(277 reference statements)
0
31
0
1
Order By: Relevance
“…Most interestingly, these parameters can be used to obtain CCs with similar thermodynamic stabilities that possess a different dynamic response to an externally applied force. Such systems will find application as molecular force sensors 41 or as physical hydrogel crosslinks, which show a pre-defined response to mechanical deformation.…”
mentioning
confidence: 99%
“…Most interestingly, these parameters can be used to obtain CCs with similar thermodynamic stabilities that possess a different dynamic response to an externally applied force. Such systems will find application as molecular force sensors 41 or as physical hydrogel crosslinks, which show a pre-defined response to mechanical deformation.…”
mentioning
confidence: 99%
“…Although early studies have been conducted on gold or glass surfaces, the technique is highly amendable for use in hydrogels as eluded to in a recent article from the group of Blank. 459 One of the major questions pertaining to the evolving field of bioprinting that remains, is to what extent spatial organization should be engineered and what should be left to the cells to self-organize? There is no doubt that most tissues require a strict organization to function but that functioning also depends on the interaction of the different cell types and tissue structures.…”
Section: Discussionmentioning
confidence: 99%
“…biomimetic hydrogels, [8] protein origami structures, [9] artificial membrane fusion domains [10] and molecular force sensors. [11] To tune the mechanical properties of synthetic CCs, a detailed understanding of their sequence-structure-mechanical relationships is crucial. We have recently shown that the helix propensity of the solvent-exposed amino acids affects the mechanical stability of a 4-heptad CC heterodimer when applying a shear force at two opposing termini.…”
mentioning
confidence: 99%